Pengaruh Motivasi Belajar, Kecerdasan Emosional Dan Lingkungan Keluarga Terhadap Hasil Belajar Pada Mata Pelajaran Pengantar Ekonomi Dan Bisnis Siswa Kelas X Smk Ardjuna 02 Arjosari Tahun Ajaran 2015/2016 - Anggun Yulia Rina Putri; Prih Hardinto; Mardono * (Universitas Negeri Malang, 2016)
In order to improve the result of class X student of SMK Ardjuna 02 Arjosari on subject Introduction to Economics and Bussiness is measured through learning motivation, emotional intelligence and family environments. This study aims to determine the effect of learning motivation, emotional intelligence and family environment on learning outcomes in subject Introduction Economics and Business. The method is used mainly quantitative explanation by the number 77 with a sample population using proportional random sampling as much as 65 students. The test results demonstrate the significance of the t test hypotheses learning motivation of 0,003, emotional intelligence of 0,001 and family environment of 0,004. While testing f 0,000 on learning outcomes. So there is a significant relationship between learning motivation, emotional intelligence and family environment on learning outcomes in subject Introduction Economics and Business. Key Words: Learning Motivation, Emotional Intelligence, Family Environment, Learning outcomes